2004
DOI: 10.1158/0008-5472.can-03-3620
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in the Urinary Bladder

Abstract: The presence of carcinoma in situ (CIS) lesions in the urinary bladder is associated with a high risk of disease progression to a muscle invasive stage. In this study, we used microarray expression profiling to examine the gene expression patterns in superficial transitional cell carcinoma (sTCC) with surrounding CIS (13 patients), without surrounding CIS lesions (15 patients), and in muscle invasive carcinomas (mTCC; 13 patients). Hierarchical cluster analysis separated the sTCC samples according to the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(143 citation statements)
references
References 29 publications
3
140
0
Order By: Relevance
“…Using the ONCOMINE program (50, 51), we have analyzed decorin mRNA levels in available microarray data sets and found that decorin expression is considerably reduced in urothelial carcinoma vis-à-vis normal bladder tissues in two independent data sets (54,55). In addition, by immunohistochemical analysis of low and high grade bladder cancer specimens, we discovered that decorin expression is almost totally lost in the tumor stroma compared with normal bladder and inversely correlates with IGF-IR levels, whose expression is markedly increased with bladder cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Using the ONCOMINE program (50, 51), we have analyzed decorin mRNA levels in available microarray data sets and found that decorin expression is considerably reduced in urothelial carcinoma vis-à-vis normal bladder tissues in two independent data sets (54,55). In addition, by immunohistochemical analysis of low and high grade bladder cancer specimens, we discovered that decorin expression is almost totally lost in the tumor stroma compared with normal bladder and inversely correlates with IGF-IR levels, whose expression is markedly increased with bladder cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…PTPD1 mRNA is up-regulated in several forms of cancer (27,28). Up-regulated EGFR signaling has been mechanistically linked to the malignant behavior of several epithelial human tumors, including bladder cancer.…”
Section: Ptpd1 Is a Component Of The Endocytic Pathway-tomentioning
confidence: 99%
“…In recent years, genome-wide expression profiling by the use of microarray technology has contributed to extensive and new insights into the complex gene expression patterns and dysregulation of genes occurring in urothelial neoplasias (Thykjaer et al, 2001;Dyrskjt et al, 2003Dyrskjt et al, , 2004Dyrskjt et al, , 2005Mor et al, 2003;SanchezCarbayo et al, 2003;Modlich et al, 2004;Blaveri et al, 2005;Kim et al, 2005;Wild et al, 2005). Microarray analyses have not only delineated gene expression profiles distinct for different histological subtypes (Thykjaer et al, 2001;Dyrskjt et al, 2003Dyrskjt et al, , 2004Sanchez-Carbayo et al, 2003;Blaveri et al, 2005;Wild et al, 2005), but also gene expression signatures of importance for tumor recurrence and progression (Dyrskjt et al, 2003(Dyrskjt et al, , 2005Modlich et al, 2004;Wild et al, 2005), and patient survival (Blaveri et al, 2005;Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Microarray analyses have not only delineated gene expression profiles distinct for different histological subtypes (Thykjaer et al, 2001;Dyrskjt et al, 2003Dyrskjt et al, , 2004Sanchez-Carbayo et al, 2003;Blaveri et al, 2005;Wild et al, 2005), but also gene expression signatures of importance for tumor recurrence and progression (Dyrskjt et al, 2003(Dyrskjt et al, , 2005Modlich et al, 2004;Wild et al, 2005), and patient survival (Blaveri et al, 2005;Kim et al, 2005). Whereas previous microarray studies of bladder cancer mostly have been dedicated to isolate gene expression profiles and predictors that classify tumors according to stage, recurrence and outcome, we focus on a comprehensive molecular characterization of Ta and T1 tumors.…”
Section: Introductionmentioning
confidence: 99%